MANUFACTURING TECHNOLOGY OF SHORT-LENGTH TUBE BILLETS BY CENTRIFUGAL CASTING - D. A. Volkov; A. D. Volkov (Литьë и металлургия)
The technologies and the small-sized machines of centrifugal casting developed by JSC «BELNIILIT» are given.